The Danger of Ghuluw: When Excessive Veneration of The Righteous Becomes a Path To Polytheism : Ketika Pengagungan Berlebihan terhadap Orang Saleh Menjadi Jalan Menuju Kemusyrikan - Mifdalulkiram, Ahmad Muwaffaq; Hilmi, Abdurrahman; Pranoto, Agung (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
Excessive reverence toward pious individuals, known as ghuluw, represents a significant theological concern within Islamic discourse. While honoring religious figures is both customary and acceptable, when such veneration exceeds appropriate bounds, it can lead to doctrinal deviations and even acts of shirk (associating partners with God). This paper investigates the origins and manifestations of ghuluw from both theological and sociocultural perspectives, illustrating how local customs and cultural influences shape perceptions of piety. It underscores the critical role of aqidah (Islamic creed) in safeguarding the integrity of Islamic belief. Employing a literature review methodology that draws upon classical and contemporary sources, the study reveals that ghuluw frequently stems from a deficient understanding of tawhid (pure monotheism). The findings highlight the urgent need for balanced and accessible theological education to prevent the emergence of excessive veneration. Ultimately, the paper argues that addressing ghuluw is essential for preserving the purity of tawhid in the daily religious life of Muslims and ensuring adherence to authentic Islamic teachings